Effect of Vortices on Jet Impingement Heat Transfer - O'DONOVAN, TADHG; MURRAY, DARINA (My University, 2006)
Convective heat transfer to an impinging air jet is known to yield high local and area averaged heat transfer coefficients. Such jets are of interest in the cooling of electronic components and of turbine blades and in manufacturing processes such as grinding. The current research is concerned with the measurement of heat transfer to impinging air jets over a wide range of test parameters. These include Reynolds numbers, Re, from 10000 to 30000, nozzle to impingement surface distance, H\D, from 0.5 to 8 and angle of impingement, , from 30? to 90? (normal impingement). The current research reports both mean and fluctuating heat transfer distributions up to 6 diameters from the geometric centre of the jet. The heat transfer results are compared to local velocity data. Spectral and coherence information is also reported for simultaneous velocity and heat flux measurement. At low nozzle to impingement surface spacings the heat transfer distributions exhibit secondary peaks at a radial location that varies with both Re and H\D. These peaks are shown to be due to an abrupt increase in turbulence in the wall jet boundary layer. At certain test configurations vortices that initiate in the shear layer impinge on the surface and move along the wall jet before being broken down into smaller scale turbulence. This vortical characteristic of an impinging air jet has also been shown to vary considerably with the angle of impingement; depending on the distance between the near nozzle edge and the impingement surface, vortices at different stages of development will impact with the target surface.
13th International Heat Transfer Conference
PUBLISHED
Sydney
Keywords: Convective heat transfer; Air jets; Heat transfer measurement